Factores asociados al consumo de bebidas energizantes, en estudiantes de la Carrera de Psicología Clínica de la Universidad Nacional de Loja - Armijos Soto, Karina del Cisne (2020)
In Ecuador there are few studies on the consumption of energy drinks in students of the Clinical Psychology degree, their importance indicates that they require staying awake, focused and with enough energy to carry out their academic tasks. The present work was carried out because we do not currently have studies that indicate the current situation of our city, the objective of this research was to find out what are the factors associated with the consumption of energy drinks, to determine the frequency of consumption. In which a descriptive, analytical and prospective cross-sectional quantitative approach study was used, carried out during the months of October 2018 to March of the year 2019. A survey-type data collection form was applied, 171 students participated, of them 74.26% consume them and 23% do not.Their consumption is related to academic activities, so 27.6% consume to decrease sleep hours, 25.2% to improve concentration, and only 3.9% consume them for physical activity, their Consumption is notable in both men and women with 83.33% - 70.80% respectively. The frequency of consumption is 1 to 3 drinks per week. The preferred energy drinks are Red Bull and V220 and the most popular combination is V220 + caffeine. Keywords: energy drinks, psychostimulants, caffeine, consumption.